2021
DOI: 10.1002/ajmg.a.62604
|View full text |Cite
|
Sign up to set email alerts
|

An examination of adaptive behavior and functional outcomes in adults with 22q11.2 deletion syndrome: A parental perspective

Abstract: 22q11.2 Deletion Syndrome (22q11DS) is a genetic syndrome caused by a chromosomal microdeletion. It affects approximately 1 in 850-992 pregnancies, and its clinical manifestations include congenital heart disease, gastrointestinal symptoms, and psychiatric illnesses. The study examined the relationship between adaptive behavior and functional outcomes, educational attainment, employment, and independent living, and whether age, gender, intellectual disability, presence of psychiatric disorder, and close friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…As a result, it is common for young people with 22q11.2DS to experience learning delays compared to their peers as they progress through the upper years of primary school in specific areas such as math, reading comprehension, and abstract reasoning [7,[9][10][11]. All of these factors may impact on young people completing their education, and in light of this, authors of a recent study in the USA examining functional outcomes for adults with 22q11.2DS found that only 51 of 101 adults had completed high school [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is common for young people with 22q11.2DS to experience learning delays compared to their peers as they progress through the upper years of primary school in specific areas such as math, reading comprehension, and abstract reasoning [7,[9][10][11]. All of these factors may impact on young people completing their education, and in light of this, authors of a recent study in the USA examining functional outcomes for adults with 22q11.2DS found that only 51 of 101 adults had completed high school [12].…”
Section: Introductionmentioning
confidence: 99%